Records Committee review for rare bird sighting of Lesser Black-backed at Red Rock Reservoir Dam, 1994 - Dinsmore, Stephen J.et al (1994)
Records Committee review for a Lesser Black-backed Gull at Red Rock Reservoir Dam in Marion County, IA on December 11, 1994. Includes a record review document with votes and three documentation forms submitted to the committee. Epson - sheet feed